(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Silica modified with propylthioethyleamine was proposed for selectively remove ions mercury from aqueous solutions. Optimum sorption conditions of Hg(II) from water by modified silica was studied and sorption-solid-photometric method for ion mercury determination (0,25–2,5 µg ml–1 ) was development.